Teachers’ Challenges and Coping Strategies in Conducting Mental Health and Psychosocial Support Activities - Tual, Concept; Omandam, Mary Jane (International Journal of Educational Innovation and Research, 2023)
Mental Health and Psychosocial Support, or MHPSS, are significant in our wellbeing. During pre-pandemic, some professionals and practitioners were trained to conduct MHPSS. However, teachers are now recognized as providers because of the wide call for the integration of MHPSS in education. Thus, the researcher aimed to explore teachers' experiences conducting MHPSS for students. The study participants are classroom teachers with one to three years of experience in the Department of Education under a teacher induction program and assigned to a school with mental health practitioners like guidance counselors and school nurses. The data is analyzed using the case study model of Meriam and Tisdell. The study revealed the circumstances where students' support, activities conducted, challenges encountered, coping strategies, and responses of the recipients. The study served as an evaluation of the support and intervention in the school setting. Practitioners may use the result of this study to identify the areas where teachers need help the most. Future researchers may examine teachers' experiences assigned to schools without mental health professionals and practitioners to identify more challenges and coping strategies.